2023
DOI: 10.3389/fcimb.2023.1027769
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial pathogens in pediatric appendicitis: a comprehensive retrospective study

Julia Felber,
Benedikt Gross,
Arend Rahrisch
et al.

Abstract: BackgroundAppendicitis is a frequent condition, with peak incidences in the second decade of life. Its pathogenesis is under debate, but bacterial infections are crucial, and antibiotic treatment remains essential. Rare bacteria are accused of causing complications, and various calculated antibiotics are propagated, yet there is no comprehensive microbiological analysis of pediatric appendicitis. Here we review different pre-analytic pathways, identify rare and common bacterial pathogens and their antibiotic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 95 publications
(113 reference statements)
2
4
0
1
Order By: Relevance
“…However, this mechanism is not observed in all cases [ 1 ]. It has also been proposed that appendiceal inflammation may be secondary to a tumor, a foreign body or an infection (viral or bacterial) [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this mechanism is not observed in all cases [ 1 ]. It has also been proposed that appendiceal inflammation may be secondary to a tumor, a foreign body or an infection (viral or bacterial) [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Antimicrobial therapy in appendicitis patients is essential for both empirical and postoperative treatment. For many surgeons, the standard has been resection alone with single-shot antibiotics, while real antibiotic treatment is only in cases of perforation or peri typhlitic abscess (1,12,14) .…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining intraoperative culture swabs (IOCS) in appendectomy patients is important to identify the pathogen and adjust the antibiotic regimen. Peña et al (13) and Felber et al (14) reported that IOCS can help in knowing antibiotic resistance patterns in a specific population or institution, and therefore guide the most effective empiric antibiotic regimen in patients undergoing LA rather than being blindly treated. In a cohort study conducted by Coccolini et al (15) on 1431 AA patients, they reported that antimicrobial resistance was strictly linked to the clinical outcome of the patients and adequate empirical antimicrobial therapy being guided by microbiological swab results is fundamental to counteract bacterial resistance and cutting down postoperative complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Несмотря на то что первое подробное исследование аппендиколита было проведено еще в 1966 г., сведения об аппендикулярных конкрементах скудны [12]. Обструкция просвета аппендикса, вызванная аппендиколитом, лимфоидной гиперплазией или отеком, считалась основной причиной аппендицита, а избыточный бактериальный рост рассматривался как следствие [13,14]. Несмотря на неопределенность в отношении последовательности событий, ведущих к развитию аппендицита, в настоящее время предполагается, что микробиом играет центральную роль в патогенезе развития воспаления.…”
Section: Introductionunclassified